The Use of Audio Visual Media As an Effort to Increase Student Motivation in Aqidah Akhlak Subjects - Anis Setiyanti; Zubairul A’lam Nur (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2021)
The learning process is a process of communication between teachers and students through verbal language as the main medium for delivering learning material. In these conditions, the learning process is very dependent on the teacher as a learning resource. However, not all learning materials can be presented by the teacher directly. To learn how living things live on the seabed, it is impossible for the teacher to guide students directly to the bottom of the ocean, or to cut open the human chest just to learn how the human organs work. However, teachers can use a variety of tools in delivering learning material. Learning aids are what is meant by media or learning aids. In learning Aqidah Akhlak, so that the learning material provided is easier for students to understand, media is needed that helps the delivery process. Through the media (aids), it is hoped that the same perception will occur between teachers and students and can increase children's learning motivation inside and outside the classroom. Moreover, Learning Aqidah Akhlak, namely education that is very important for human life, especially in achieving inner peace and mental health in general. Audio Visual media can be used as an alternative to learning Akidah Akhlak to make it easier for children to increase motivation in learning.Keywords: Audio Visual Media, Learning Aqidah Akhlak, and Motivation